KOMUNIKASI PEMASARAN COFFEE SHOP DALAM SITUASI PANDEMI COVID-19 (Studi Kasus Work Coffee Indonesia Di Bandung) - Devi Rahmawati; Pandi Pardian; Iwan Setiawan; Agriani Hermita Sadeli (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The number of coffee shops has increased over the past five years. It is driven by the change of the lifestyle of today’s society who chose coffee shops as a place to do activities such as meeting, discussions, working on assigments, etc. The presence of the covid-19 pandemic since the beginning of 2020 also making an impact on various types of businesses including coffee shop. Work coffee indonesia is one of the coffee shops that exposed the impact of the covid-19 pandemic. Although being exposed by the impact of the pandemic, work coffee indonesia still able to survive by doing various promotional activities. Marketing communication becomes one of the tools to maintain the market of business. Therefore this research aims to find out about coffee shop marketing communication in facing the covid-19 pandemic with the work coffee indonesia case study. The method used in this research is qualitative with a descriptive-qualitative design with a research technique used is a case study. It is known in this research that the importance of marketing communication role in maintaining a business and expanding consumer market particularly while experiencing unforseen circumstances such as covid-19 pandemic.